Penerbangan dan Wisata: Travel Bubble dan Koridor Transportasi di Masa Pandemi - Agung Wahyu Wicaksono; Imam Sonhaji; Darmawanta Sembiring (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
The purpose of this study is to examine Indonesia's readiness in implementing the Travel Bubble, map which countries are most appropriate for a travel bubble based on the covid case that occurs and to map safe transportation corridors to leading tourist destinations in Indonesia. The research method used is qualitative research method by describing statistical data to draw conclusions, the data used are secondary data published by related organizations and previous research data related to this research. The results of this study explain that Indonesia is still not ready for the existing conditions, it needs other adjustments, while the best countries for a travel bubble with Indonesia are China, Singapore, the Netherlands and Saudi Arabia. Covid-19 free transportation corridors that can be mapped are the Yogyakarta - Bali - Lombok - Komodo Island corridor, the Bali - Toraja corridor via Makassar and the Bali - Raja Ampat corridor via Biak